A comparison of farmers’ perceptions and meteorological data on climate change in northwestern Ghana - Dramani Juah M-Buu File; Godwell Nhamo (Cogent Social Sciences)
Climate change is mostly perceived by smallholder farmers in terms of changes in weather elements such as rainfall and temperature. These changes are typically observed over time in an immediate environment. Studies have largely focused on examining smallholder farmers’ perceptions of climate change, with little attention paid to comparisons between farmers’ perceptions and scientific meteorological data. This study compared smallholder farmers’ perceptions with meteorological data on rainfall and temperature in northwestern Ghana. This study employed mixed methods for data collection and analysis. A survey was conducted among 305 household heads using a questionnaire instrument, and in-depth interviews and focus group discussions were conducted among selected key participants. The results showed perceived changes in rainfall, such as a decreasing rainfall pattern, late onset, early cessation, limited coverage and distribution, and increasing uncertainty and unpredictability. Temperatures were perceived to increase with extreme heat conditions and a long duration of the hot season. The meteorological data mostly corroborated the perceptions of smallholder farmers regarding changes in rainfall and temperatures at the municipal, regional, and national scales. The study concluded that both scientific data and farmers’ perceptions point to increasing changes in rainfall and temperature. Therefore, farmer perceptions should be mainstreamed into meteorological data analysis to inform policymaking discourse towards effective and sustainable climate-compatible agricultural planning in Ghana.